Composition of volcanic tephra, Haungaroa volcano - Diehl, Alexander; Bach, Wolfgang (PANGAEA, 2020)
XRF measurement of bulk rock composition of sample SO253-035-ROV15M recovered during RV Sonne expedition SO253 (Kermadec arc).
Keywords: bulk-rock-composition; Haungaroa volcano; Kermadec; RV Sonne SO253; Tephra; volcanic sediment